2011
DOI: 10.1039/c1py00063b
|View full text |Cite
|
Sign up to set email alerts
|

Architecture effects on L-selectin shedding induced by polypeptide-based multivalent ligands

Abstract: Multivalent interactions between selectins and their ligands play key roles in mediating the rolling and tethering of leukocytes in the early steps of the inflammatory response, as well as in lymphocyte circulation. L-selectin shedding, which is the proteolytic cleavage of L-selectin, can be induced by L-selectin clustering through the binding of multivalent ligands to multiple L-selectin molecules, and it has been shown to regulate leukocyte rolling and subsequent integrin activation for firm adhesion. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…2). Ligand density is known to act as a potent driver of shedding (43)(44)(45), and an increasing gradient of HSPG-like ligands across postcapillary venules could therefore influence L-selectin shedding. Also, a lack of shear stress in the subendothelial space could dramatically influence L-selectin clustering and subsequent signaling events that could feedback to activate ADAM17 locally and drive the shedding response specifically in pseudopods.…”
Section: Discussionmentioning
confidence: 99%
“…2). Ligand density is known to act as a potent driver of shedding (43)(44)(45), and an increasing gradient of HSPG-like ligands across postcapillary venules could therefore influence L-selectin shedding. Also, a lack of shear stress in the subendothelial space could dramatically influence L-selectin clustering and subsequent signaling events that could feedback to activate ADAM17 locally and drive the shedding response specifically in pseudopods.…”
Section: Discussionmentioning
confidence: 99%
“…148 Using a polypeptide backbone, sialylated ligands were appended to give a polymer with ligands separated by distances estimated to range from 17 – 35 Å and a polymer with carbohydrate moieties separated by 35 – 50 Å. The polymer with shorter carbohydrate-spacing was more effective at eliciting L-selectin shedding than the polymer with the longer spacing.…”
Section: Mimics Of Surface Glycansmentioning
confidence: 99%
“…It should also be noted that studies of L-selectin monovalent and bivalent aptamers have not demonstrated shedding [ 4 6 ]. Interestingly, synthetic multivalent carbohydrate ligands only induced shedding of L-selectin at millimolar concentrations while blocking L-selectin function at micromolar concentrations [ 9 ]. It has been hypothesized that shedding of L-selectin by multivalent ligands depends on both the number of ligands as well as the distance between the ligands [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, synthetic multivalent carbohydrate ligands only induced shedding of L-selectin at millimolar concentrations while blocking L-selectin function at micromolar concentrations [ 9 ]. It has been hypothesized that shedding of L-selectin by multivalent ligands depends on both the number of ligands as well as the distance between the ligands [ 9 ]. In the future, we plan to tailor the parameters of the LS-Multi-Aptamer to directly determine if the physical properties of the Multi-Aptamers can be optimized to mediate shedding versus blocking.…”
Section: Resultsmentioning
confidence: 99%